Nepal country brief - Cunningham, Kenda; Singh, Akriti; Headey, Derek D.; Pandey Rana, Pooja; Karmacharya, Chandni (Transform Nutrition, 2016)
This brief summarises the findings from a research study – Stories of Change in Nutrition in Nepal – which is about how Nepal rapidly reduced undernutrition among children under 2 years of age and their mothers. This Nepal study specifically aims to answer three questions: 1) What were the drivers of reductions in maternal and child undernutrition? 2) What were the key policies and programs in Nepal behind these drivers? and 3) What challenges and opportunities face Nepal to further reduce undernutrition (including those related to the Multi-sector Nutrition Plan)?